Translating thyroid hormone into clinical practice: lessons learned from the post-hoc analysis on data available from the ThyRepair study - Pantos, Constantinos I.; Grigoriou, Konstantinos P.; Trikas, Athanasios G.; Alexopoulos, Nikolaos A.; Mourouzis, Iordanis S. (Frontiers in Endocrinology, 2024)
Background: Thyroid hormone (TH) appears to have a reparative action on the postinfarcted myocardium. This novel action was recently tested in a pilot, randomized, double blind, placebo controlled trial (ThyRepair). The present study performed a post hoc analysis on data from the ThyRepair study to provide further insights into the novel actions of TH on human postischemic myocardium.Methods: Data from 41 patients participating in the ThyRepair study (n=20 placebo and n=21 LT3) were included in analysis. LT3 treatment started after stenting and continued intravenously for 48 hours. All patients had CMR at hospital discharge and left ventricular (LV) ejection fraction (LVEF%), LV end-diastolic volume index (LVEDVi, ml/m 2 ), LV end-systolic volume index (LVESVi, ml/m 2 ), Infarct Volume (IV), LVMi as edema index and microvascular obstruction (MVO) were assessed. Patients were divided in two groups based on the median value of the IV; patients with IV≤20% of the LV (group A) and patients with IV>20% (group B). CMR measurements at discharge expressed as mean±SD.In group A, placebo and T3-treated group had similar LVEF% (56.8±10.2 vs 52.2±10.5), LVEDVi (90.9±19.8 vs 92.8±14.5) and LVESVi (40.8±18.2 vs 44.9±14.1) at discharge. In group B, LVEDVi and LVESVi were 112±23.8 and 68.3±21.5 for placebo vs 91.8±18.6 and 49.0±14.0 for T3 group respectively, p<0.05. Furthermore, LVEF% was significantly increased in T3 treated group vs placebo, 47.3±6.5 vs 39.9±8.7, p<0.05. In group B, CMR LVMi was lower in T3-treated patients vs placebo, but did not reach statistical significance (p=0.1). MVO was 1.95±2.2 in placebo vs 0.84±0.9 in LT3 treated group, p=0.15. The present study suggests that acute LT3 treatment may exert more favourable effects on the recovery of cardiac function in patients with large infarct size. Furthermore, it signals for a potential effect of LT3 on myocardial edema and microvascular obstruction. These novel findings merit further investigation in large trials.